2011
DOI: 10.5021/ad.2011.23.1.53
|View full text |Cite
|
Sign up to set email alerts
|

A Two-week Interval Is Better Than a Three-week Interval for Reducing the Recurrence Rate of Hand-foot Viral Warts after Cryotherapy: A Retrospective Review of 560 Hand-foot Viral Warts Patients

Abstract: Background: Viral warts are a common infectious disease and liquid nitrogen cryotherapy is one of the most common methods for treatment of these warts. Hand-foot viral warts frequently recur and reduce quality of life as well. Objective: To find the ideal treatment interval between cryotherapy sessions that can influence not only the cure rate but also the recurrence rate for hand-foot viral warts. Methods: A retrospective study was designed to compare a 2 week interval and a 3 week interval between cryotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
(33 reference statements)
2
23
0
Order By: Relevance
“…Still, costs for treatment of warts could be greatly reduced, as only limited treatment sessions (median number of 3) are needed to achieve complete resolution of warts in children compared to cryotherapy. In addition, the recurrences reported for CPS1 solution (10.6 and 19.4% for children and adults, respectively) are roughly lower or comparable to other treatments of cutaneous warts with duct tape (75%), cryotherapy (13.3–25%), 5% 5‐fluorouracil (13–15%), and pulsed dye laser (0–36%; Dhar, Rashid, Islam, & Bhuiyan, ; Gladsjo et al, ; Salk et al, ; Veitch, Kravvas, & Al‐Niaimi, ; Wenner et al, ; Youn, Kwon, Park, Kim, & Kim, ). Two studies reported no recurrences after treatment of cutaneous warts with CPS2 solution (Table ) (Becerro de Bengoa Vallejo et al, ; Kaçar et al, ).…”
Section: Discussionmentioning
confidence: 77%
“…Still, costs for treatment of warts could be greatly reduced, as only limited treatment sessions (median number of 3) are needed to achieve complete resolution of warts in children compared to cryotherapy. In addition, the recurrences reported for CPS1 solution (10.6 and 19.4% for children and adults, respectively) are roughly lower or comparable to other treatments of cutaneous warts with duct tape (75%), cryotherapy (13.3–25%), 5% 5‐fluorouracil (13–15%), and pulsed dye laser (0–36%; Dhar, Rashid, Islam, & Bhuiyan, ; Gladsjo et al, ; Salk et al, ; Veitch, Kravvas, & Al‐Niaimi, ; Wenner et al, ; Youn, Kwon, Park, Kim, & Kim, ). Two studies reported no recurrences after treatment of cutaneous warts with CPS2 solution (Table ) (Becerro de Bengoa Vallejo et al, ; Kaçar et al, ).…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, Khaled et al observed higher cure rate among patients with hand warts than those with foot warts. On the contrary, Youn et al reported better results among foot warts than hand warts.…”
Section: Discussionmentioning
confidence: 94%
“…[34][35][36][37] However, the cure rates after 6 months are often similar, suggesting that clearance may in fact depend on the total number of treatments given. Only one randomized trial has explored the total number of treatments, and even this trial was not ideally designed to answer this question.…”
Section: 29mentioning
confidence: 99%